Birth outcomes of advanced maternal age pregnancies - Diabelková, Jana; Dorko, Erik; Rimárová, Kvetoslava; Urdzík, Peter; Sulinová, Zlatana; Houžvičková, Andrea; Kopecký, Miroslav (Central European journal of public health, 2024)
OBJECTIVE: Pregnancy at advanced maternal age has become more common over the last decades. Therefore, the study aimed to describe the characteristics and maternal and perinatal outcomes of women giving birth at advanced maternal age and very advanced age. METHODS: We conducted a retrospective cohort study of 2,300 singleton births that occurred in 2020-2021 at the Department of Gynaecology and Obstetrics of the Louis Pasteur University Hospital in Košice. The control (age 20-34 years), advanced maternal age (35-39 years), and very advanced maternal age (≥ 40 years) groups included 1,851, 382, and 67 women, respectively. Exclusion criteria were multiple pregnancies, maternal age less than 20 years, smoking and alcohol use, foetal malformation and intrauterine foetal death, and birth weight of 500 grams or less. Data on mothers and newborn infants have been reported from the birth book and the reports on mothers at childbirth. The data were analysed using IBM SPSS Statistics 23.0. RESULTS: Our results confirmed statistically significant differences regarding the rate of preterm birth (p = 0.004), very preterm birth (p = 0.010), caesarean delivery rate (p < 0.001), very low birth weight (p = 0.027), extremely low birth weight (p = 0.001), and Apgar score at 5 minutes < 7 (p = 0.020) between newborns in the compared maternal age groups. CONCLUSION: Advanced maternal age is a prognostic factor for poor pregnancy outcomes. Women of advanced maternal age are at higher risk of adverse obstetric and perinatal outcomes.
Keywords: Cesarean Section; preterm birth; risk factors; Retrospective Studies; těhotenství; Advanced Maternal Age; Premature Birth; výsledek těhotenství; pokročilý věk matky; Adult; mladý dospělý; věk matky; císařský řez; Infant, Newborn; birth outcomes; Young Adult; ženské pohlaví; novorozenec; předčasný porod; retrospektivní studie; Humans; Pregnancy; Pregnancy Outcome; advanced maternal age; very advanced maternal age; dospělí; Female; birth weight; lidé; Maternal Age